BUILDING FOOD INDEPENDENCE: IMPLEMENTATION CHRONICLES OF SUSTAINABLE FOOD HOUSE AREAS: ISBN 978-630-95064-1-2 - Hutapea, Yanter (Technium Books, 2024)
The book: BUILDING FOOD INDEPENDENCE: IMPLEMENTATION CHRONICLES OF SUSTAINABLE FOOD HOUSE AREAS ISBN 978-630-95064-1-2 is published in Technium.